RELIGIOUS SOCIALISM GIVES BIRTH TO A DYNAMIC WORLD: A CRITICAL REVIEW OF DIALECTICAL MATERIALISM AND HISTORICAL MATERIALISM - Anindya Puspita (Universitas Pendidikan Indonesia, 2022)
This study discusses Indonesian scholar, Abdullah bin Nuh, criticism on Karl Marx’s materialism concept. He argued that this theory is a symbiosis of capitalism and secularism that lead to communism. The theory aims to refract the existence of God and may produce authoritarian and dictatorial rulers. The researcher used a qualitative approach with the literature review method. Nuh's essay on Islam and Materialism firmly explores and scrutinizes Marx’s historical and dialectical materialism by employing several approaches including philosophical, scientific, and scientists’ opinions. According to Nuh offered a new balanced concept that is also in harmony with religion, which is religious socialism that has to be freed from atheism and materialism